10 Manganese-enhanced T1 mapping in myocardial infarction: validation with 18F-FDG PET/MR. (May 2018) - Spath, Nick B; Tavares, Adriana; Gray, Gillian A; Dweck, Marc R; Newby, David E; Yang, Phillip C; Jansen, Maurtis A; Semple, Scott I
Abstract : Introduction: Manganese-enhanced magnetic resonance imaging (MEMRI) is a promising non-invasive imaging tool in viability and cardiomyopathy, quantifying infarct size more accurately than late-gadolinium enhancement, as we previously demonstrated. We aimed to validate MEMRI viability against 18 F-FDG positron emission tomography (PET). Methods: Sprague-Dawley rats (male; 180–300 g) underwent permanent surgical anterior myocardial infarction (n=11), or sham surgery (n=2), with dual MEMRI and 18F-FDG PET assessment at 12 weeks. MEMRI (7 T spectrometer, Agilent, UK) was achieved with intravenous manganese gluconate (EVP1001–1, Eagle-Vision-Pharmaceuticals, USA; n=6, 22 μmol/kg) and mangafodipir (Teslascan, IC-Targets, Norway; n=7, 44 μmol/kg). Anatomical and functional imaging preceded cardiac-gated Modified Look-Locker Inversion recovery (MoLLI) before and 20 min post-contrast (at maximal infarct slice). Commercially available software generated standardised T1 maps for ROI-contouring. For PET imaging, intravenous 18 F-FDG (20–30 MBq) was administered with PET data acquired for 60 min, followed by cardiac-gated acquisition (10 min). PET/MR images were co-registered and fused for analysis. Results: Infarct size assessed by MEMRI T1 mapping was smaller than by native T1 at 12 weeks (mean 23.34 vs 18.68%; p=0.001). Native T1 mapping consistently overestimated infarct size (bias 25.76; 95% CI: 7.51 to 44.01; p=0.031) but there was excellent agreement between MEMRI T1 mapping and 18 F-FDG (bias 1.30; 95% CI: −24.98 to 25.57; p=0.7). Post-MEMRI T1 values showed negative trend with increasing SUV (r 2 =0.25, p=0.08) whereas native T1 demonstrated no relationship (r 2 =0.0001, p>0.9). Conclusion: MEMRI T1 mapping identifies viable myocardium as well as 18 F-FDG PET and was superior to native T1 mapping. Post-MEMRI T1 appears related to SUV where native T1 does not. This validation data informs the clinical translation of cardiac MEMRI.